Pentingnya Perlindungan Hukum Bagi Korban Tindak Pidana Penipuan dalam Proses Transaksi Jual Beli Secara Online (E- Commerce ) - Maya Sri Novita (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
The development of information technology has encouraged the rapid growth of online buying and selling (e-commerce) activities. However, along with the increase in digital transactions, fraud in e-commerce is increasingly prevalent. This research aims to examine the importance of legal protection for victims of fraud in online transactions and examine the effectiveness of applicable laws and regulations in providing justice and legal certainty. The research method used is a normative juridical approach with an analysis of laws and regulations, legal literature, and case studies. The results of the study show that despite the existence of legal instruments such as the Criminal Code, the ITE Law, and the Consumer Protection Law, the implementation of protection for victims still faces various obstacles, such as the difficulty of tracking perpetrators and weak law enforcement. Therefore, it is necessary to strengthen regulations, increase public legal literacy, and optimize the role of law enforcement officials in providing maximum protection to victims of fraud in e-commerce. This research recommends synergy between regulation, technology, and education as an effective legal protection solution in the digital era.